2017
DOI: 10.1038/srep44778
|View full text |Cite
|
Sign up to set email alerts
|

A smartphone-based diagnostic platform for rapid detection of Zika, chikungunya, and dengue viruses

Abstract: Current multiplexed diagnostics for Zika, dengue, and chikungunya viruses are situated outside the intersection of affordability, high performance, and suitability for use at the point-of-care in resource-limited settings. Consequently, insufficient diagnostic capabilities are a key limitation facing current Zika outbreak management strategies. Here we demonstrate highly sensitive and specific detection of Zika, chikungunya, and dengue viruses by coupling reverse-transcription loop-mediated isothermal amplific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
229
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(231 citation statements)
references
References 46 publications
1
229
0
1
Order By: Relevance
“…Furthermore, in this study, positive and negative controls were used in all the reactions to assure not having contamination problems. The advantage of observing the results by real-time allows the diagnosis in less than 30 min, so that treatment and care to avoid transmission of the disease can start immediately [23]. Studies already reported ZIKV transmission through sexual [2], perinatal [3] and blood transfusion [4].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in this study, positive and negative controls were used in all the reactions to assure not having contamination problems. The advantage of observing the results by real-time allows the diagnosis in less than 30 min, so that treatment and care to avoid transmission of the disease can start immediately [23]. Studies already reported ZIKV transmission through sexual [2], perinatal [3] and blood transfusion [4].…”
Section: Discussionmentioning
confidence: 99%
“…[4] While reverse transcription PCR (RT-PCR) is often used as aN AT,R T-LAMP has also been extensively used for virus detection owing to its robustness,h igh sensitivity and specificity,s hort incubation time,a nd simplified thermal management. [7][8][9][10][11][12][13][14] Although RT-LAMP allows virus samples to be used for amplification without sample preparation, the small sample volume and dilution steps involved decrease detection sensitivity. [7][8][9][10][11][12][13][14] Although RT-LAMP allows virus samples to be used for amplification without sample preparation, the small sample volume and dilution steps involved decrease detection sensitivity.…”
mentioning
confidence: 99%
“…Automating the S value calculation can be an alternative way of improving PAD sensitivity. Many previous studies have demonstrated the benefits of a smartphone for reading and obtaining a quantitative and objective result for an accurate diagnostic . For the first version of the PAD, an Android‐based application was developed on a smartphone for reproducible and quantitative results from the raw signals.…”
Section: Discussionmentioning
confidence: 99%